Post Lockdown and Teaching: Problems Faced by Primary Teachers in Lahore, Pakistan - Muhammad Anwar; Oqba Khan; *Rashid Mustafa (Research Journal of Psychology, 2024)
The research aims finds problems faced by the primary school teachers in Lahore district after the outbreak of covid-19. All education system was affected but teachers of primary education were facing different kinds of problems in teaching. The study was delimited to male and female English subject teachers of primary schools of Lahore district. A quantitative nature of the study and survey method used for data collection. The study was quantitative therefore the population of the study mainly consisted of all male and female primary school English teachers of Lahore district Punjab, Pakistan. The sample of 100 male and 100 female teachers were taken by using convenient sampling technique. A five-point Likert scale research instrument was utilized to conduct the study. The researcher personally distributed the questionnaires among as many primary school teachers in Lahore district as possible. For female teachers, assistance from relative female teachers was sought to facilitate the distribution process. Data analysis involved descriptive statistics, including mean and standard deviation, as well as inferential statistics through an independent samples t-test. It was concluded that post lockdown both male and female primary school teachers of Lahore district faced problem like environment disturbance, classroom discipline, fair of virus, lack of prevention facilities, lack of management, lack of collaboration, lack of student’s assessment, lack of examination, lack of student’s motivation and problems of SOPs. Key Words: Post Lockdown, Teaching, Problems Faced , Primary Teachers Lahore, Pakistan